Efektivitas Komunikasi Persuasif dalam Siaran Puja Tri Sandhya TVRI Bali terhadap Minat Sembahyang Siswa SMA Negeri 1 Gianyar - Gayatri, Sintyananda; Segara, I Nyoman Yoga; Yuliani, Ni Made (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2019)
The TVRI Bali Public Broadcasting Institution (LPP) as one of the local broadcasting television stations owned by the Government of the Province of Bali, also functions as an extension media by displaying religious broadcasts. One of the religious broadcasts that must be aired on TVRI Bali is Puja Tri Sandhya. Like advertising, the broadcast of Puja Tri Sandhya, which is aired every day, is expected to have an effect, which is to persuade the audience to be able to raise self-awareness to pray. Based on the researcher's personal observation, the phenomenon is that there are still many Hindus who especially in Bali have not been diligent in carrying out the Tri Sandhya Puja three times a day. Therefore, this study aims to determine the effect of the relationship between the effectiveness of persuasive communication in Tri Sandhya TVRI Bali Broadcasting Ceremony on public interest.The community group that the researchers rated was appropriate to be the target of the study were high school students (SMA) students of SMA Negeri 1 Gianyar, considering they were part of Generation Z who now tend to use gadgets rather than television. This study is looking at the relationship between the variable effectiveness of persuasive communication Tri Puja Sandhya (X) on the variable of student prayer interest (Y).Based on the results of the analysis of the effect of the persuasive communication effectiveness variable in the broadcast of Tri Sandhya (X) Puja on the variable of prayer interest in students of SMA Negeri 1 Gianyar (Y), it can be concluded that the persuasive communication effectiveness variable in the Tri Sandhya (X) Puja broadcast proved to have a significant effect on variable interest in prayer for students of SMA Negeri 1 Gianyar(Y) of 0,889 or as much as 92.1%.